2021
DOI: 10.3389/fnbeh.2021.755373
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Activity of Choline Acetyltransferase From Different Synaptosomal Fractions at the Distinct Stages of Spatial Learning in the Morris Water Maze

Abstract: Accumulated data have evidenced that brain cholinergic circuits play a crucial role in learning and memory; however, our knowledge about the participation of neocortical and hippocampal cholinergic systems in spatial learning needs to be refined. The aim of this study was to evaluate the association of the activity of membrane-bound and soluble choline acetyltransferase (ChAT) in the synaptosomal sub-fractions of the neocortex and hippocampus with performance of the spatial navigation task in the Morris water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…This is an important and interesting problem. Rats that are incapable of the consolidation of spatial memory during the course of learning (4 days), after a two-week break show the high abilities for memory consolidation [ 17 ], the mechanisms of which are unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is an important and interesting problem. Rats that are incapable of the consolidation of spatial memory during the course of learning (4 days), after a two-week break show the high abilities for memory consolidation [ 17 ], the mechanisms of which are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Our biochemical data on the ratio of cholinergic activity in the ‘light’ and ‘heavy’ fractions of synaptosomes in both brain structures are in good agreement with these data [ 16 ]. In addition, in our studies we have revealed functional differences (differences in response to the experimental effects) in cholinergic presynapses from light and heavy synaptosomes [ 16 , 17 , 18 , 19 ]. This approach has allowed for a high probability that interneuron presynapses are concentrated in the heavy synaptosomes and, thus, a differentiated study of cholinergic indicators in these synaptosomes makes it possible to identify the individual contribution of different populations of cholinergic neurons to the studied functions.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Ach was then added to the buffer. After which, sodium tetraphenylborate was added and the organic phase was separated and measured by beta counter [ 31 ].…”
Section: Methodsmentioning
confidence: 99%